Effects of mifepristone on proliferation of human gastric adenocarcinoma cell line SGC-7901 in vitro - Li, Da-Qiang (World J Gastroenterol, 2004)
AIM: To explore the effects of mifepristone, a progesterone receptor (PR) antagonist, on the proliferation of human gastric adenocarcinoma cell line SGC-7901 in vitro and the possible mechanisms involved. METHODS: In situ hybridization was used to detect the expression of PR mRNA in SGC-7901 cells. After treatment with various concentrations of mifepristone (2.5, 5, 10, 20 μmol/L) at various time intervals, the ultrastructural changes, cell proliferation, cell-cycle phase distribution, and the expression of caspase-3 and Bcl-X(L) were analyzed using transmission electron microscopy (TEM), tetrazolium blue(MTT) assay, (3)H-TdR incorporation, flow cytometry, and reverse transcription-polymerase chain reaction (RT-PCR). RESULTS: Mifepristone markedly induced apoptosis and inhibited cell proliferation of PR- positive SGC-7901 cells revealed by TEM, MTT assay and (3)H-TdR incorporation, in a dose- and time-dependent manner. The inhibitory rate was increased from 8.98% to 51.29%. Flow cytometric analysis showed mifepristone dose-dependently decreased cells in S and G(2)/M phases, increased cells in G(0)/G(1) phase, reduced the proliferative index from 57.75% to 22.83%. In addition, mifepristone up-regulated the expression of caspase-3, and down- regulated the Bcl-X(L) expression, dose-dependently. CONCLUSION: Mifepristone effectively inhibited the proliferation of PR-positive human gastric adenocarcinoma cell line SGC-7901 in vitro through multiple mechanisms, and may be a beneficial agent against human adenocarcinoma.